PELATIHAN MEMBUAT KARYA MONTASE DAN MENGHIAS KELAS DI SEKOLAH DASAR AL ZAHRA INDONESIA PAMULANG - Heru Budi Kusuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Al Zahra Indonesia Elementary School is located at Jalan Vila Dago Boulevard Blok G, Benda Baru Village, Pamulang District, South Tangerang City, Banten Province. Al Zahra Elementary School currently has 24 local classes for teaching and learning activities where each level has 4 parallel classes. In addition, this school is also equipped with facilities that support teaching and learning activities, namely a library, computer laboratory, science laboratory, hall, indoor swimming pool, outdoor basketball court, indoor badminton court, administration room, teacher room, and principal's room. His deputy. Elementary school students in the curriculum are taught the subjects of Arts, Culture and Skills where for each grade level different levels of difficulty are learned. Art, Culture and Skills lessons for grade 4 include lessons on making montage works. According to the Big Indonesian Language Dictionary, montage is making a work with a composition of images resulting from mixing elements from several sources so as to produce a new work. In teaching students to be creative, sometimes teachers are constrained by creative ideas to be creative, so we need to play an active role in increasing the creativity of teachers so that in conveying material, making works of art can be more developed and produce diverse works. Making montage works can help students in expressing creative ideas, expressing their emotions which can lead to a sense of satisfaction, and provide pleasure so as to reduce the psychological burden that may arise due to online learning activities